Quantitative Analysis of Apparent Diffusion Coefficient for Disease Assessment in Paediatric Inflammatory Bowel Disease. Issue 3 (March 2019) - Scionti, Alessandra; Di Maurizio, Marco; Basile, Massimo; Bernardini, Azzurra; Miccoli, Mario; Lionetti, Paolo; Defilippi, Claudio; Caramella, Davide
ABSTRACT: Objective: The aim of the study was to establish an apparent diffusion coefficient (ADC) cut-off value to classify active and non-active lesions in inflammatory bowel disease. Methods: We reviewed 167 paediatric magnetic resonance enterographies executed for suspected inflammatory bowel disease by using a 1.5- and 3-T scanner. We assessed the presence and activity of the disease by using morphologic and functional parameters such as the ADC. Each patient could have more than 1 examinations. Quantitative assessment of disease activity in the ADC map was measured placing 3 regions of interest in the areas of highest inflammation and the mean value was calculated, patients without sign of inflammation were assessed at 2 standardised site. Ileocolonoscopy, esophagogastroduodenoscopy, surgery, and video-capsule endoscopy were used as standards of reference. Results: We enrolled 34 patients and 35 examinations: radiological findings of disease were identified in 29 examinations and 44 lesions were detected. Six patients had negative results and ADC assessment was taken at the terminal ileum and cecum. A total of 56 bowel segments were included in the study. Image analysis revealed 39 active lesions (69.6%) and their ADC values were lower compared to the ones of non-active segments. For each scanner a cut-off value was found (sensitivity: 0.91, specificity: 0.89 for 1.5 T and 0.81 for 3 T). Inter-rater agreement on disease activity between ADC values and magnetic resonance enterography results and between ADC values and the standard of reference were very good. Conclusions: ADC can provide a scanner-based quantitative measurement of disease activity. Abstract : Supplemental Digital Content is available in the text